Public disclosure (in whistleblower protection systems) - Sierra-Rodríguez, Javier (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
Leaks to the press are one of the common methods through which irregularities and cases of corruption in the public and private sectors have been exposed. With the approval of Spanish Law 2/2023 on the protection of whistleblowers, a modality called «public disclosure» has been regulated, necessitating its conceptualization due to its different scope and its focus on information known within a professional or work environment. Under this premise, we relate the whistleblowing system regulated by Law 2/2023 to the exercise of the freedoms of expression and information. From there, we proceed to redefine what should be understood by public disclosure within the framework of this law, explaining its conditions and reflecting on its implications. The essence of this public disclosure is that, under certain circumstances, turning to the press or other means to make information about violations available to the public will allow access to the specific protection regime of this Law, without prejudice to the protection that such actions have under the exercise of the freedoms of expression and information.